Penalaran Proporsional dalam Pendidikan Matematika: Tinjauan Literatur Sistematis (SLR) - Prismadian Amalia Putri; Agus Susanta; Nurul Astuty Yensy (Mandalika Mathematics and Educations Journal, 2025)
This systematic literature review analyzes international evidence on proportional reasoning (PR) in K–12 education and teacher training. We synthesized eight studies and identified four key patterns. Contexts with hands-on activities help students transition from intuitive to formal strategies. Students often succeed with probability ratios, but struggle with visual biases. Example-based practice with self-explanation improves probabilistic reasoning, especially for less prepared students. Finally, diagnostic tools such as construct maps are useful for tracking student progress from "combined unit" to "multiplicative comparison" understanding. Our review recommends designing a clear progression for ratios, rates, and probabilities; teaching anti-bias strategies; embedding routines of example problems; and using construct map-guided assessments. This synthesis provides a clear action lens to improve PR instruction by integrating student cognition, task design, and teacher practices.